The soft-bodied biota of the Cambrian Series 2 Parker Quarry Lagerstätte of northwestern Vermont, USA. (July 2022) - Pari, Giovanni; Briggs, Derek E.G.; Gaines, Robert R.
Abstract: A non-biomineralized arthropod, Protocaris marshi, was described from the lower Cambrian (Dyeran Series 2, Stage 4) of Parker's Cobble in northwestern Vermont in 1884. It represents the first fossil exhibiting Burgess Shale-type preservation to have been discovered. The locality was presumed to have been worked out and was not collected in a significant way for more than 100 years. Rediscovery of productive layers has yielded soft-bodied and lightly sclerotized taxa new to the locality, including the alga Fuxianospora, a possible priapulid, a radiodont, and a specimen tentatively assigned to Herpetogaster . New specimens of the sponge Leptomitus zitteli, the bivalved arthropod Tuzoia, and the chordate Emmonsaspis cambrensis provide additional information on those taxa, and multiple specimens allow a bivalved arthropod, Vermontcaris montcalmi new genus, new species, to be described. The primary mode of fossil preservation is as carbonaceous compressions. The Parker Quarry Lagerstätte complements the Kinzers Formation of Pennsylvania (also Series 2, Stage 4) in revealing the diversity of soft-bodied taxa on the southern margin of the paleocontinent Laurentia. UUID: http://zoobank.org/2eb3ae7c-6579-403e-a9ab-654c05af4a1b